Polymorphism in epidermal growth factor is related to clinical outcomes of metastatic colorectal cancer patients treated with cetuximab: a systematic review and meta-analysis - Lu, Xiaoli (Int J Clin Exp Med, 2015)
Numerous studies focusing on genetic variants in order to find cetuximab subpopulation biomarkers have emerged, yet the significance of each biomarker is diverse. Based on these results, we carried out a meta-analysis to assess the correlation between epidermal growth factor (EGF) A61G polymorphism and clinical outcomes of metastatic colorectal cancer (mCRC) patients treated with cetuximab. We aim to prove that EGF polymorphisms may be potential biomarkers for cetuximab therapeutic strategies. We identified 6 previously published studies including 569 patients treated with cetuximab-based regimens. Outcomes included clinical response, progression-free survival (PFS), and overall survival (OS). GG homozygote showed association with better response rates (GG vs. AA+AG, OR = 2.82; 95% CI = 1.58-5.04) and than AA+AG genotypes. This meta-analysis showed that mCRC patients harboring GG genotype of EGF A61G polymorphism inclined to have a better response rate with cetuximab treatment.